Thermal and Hydrothermal Treatment of Silica Gels as Solid Stationary Phases in Gas Chromatography - Ashraf Yehia El-Naggar (Journal of Analytical Methods in Chemistry)
Silica gel was prepared and treated thermally and hydrothermally and was characterized as solid stationary phase in gas chromatography. The characteristics have been evaluated in terms of polarity, selectivity, and separation efficiencies. These parameters were used to assess the outer silica surface contributions and the degree of surface deactivation brought about by different treatment techniques. The parent silica elutes the paraffinic hydrocarbons with high efficiency of separation and elutes aromatic hydrocarbons with nearly good separation and has bad separation of alcohols. The calcined silica at 500°C and 1000°C has a pronounced effect on the separation of aromatic hydrocarbons compared with the parent silica and hydrothermal treatment of silica. With respect to alcohols separation, the obtained bad separations using treated and untreated silica reflect the little effect of the thermal and hydrothermal treatment on the silica surface deactivation.